Determinación de las propiedades físico-químico del suelo del lote número 5 de la Universidad Técnica de Cotopaxi, Campus Salache mediante el uso de técnicas de prácticas básicas de laboratorio de suelo en el año 2023-2024 - Herrera Oñate, Angélica Guillermina (2024)
The present investigation was carried out in the laboratories of the Technical University of Cotopaxi of the Faculty of Agricultural Sciences and Natural Resources, whose objective is the determination of the physical and chemical properties of the soil of lot number 5 of the Technical University of Cotopaxi, Campus Salache, with the use of different methodologies which were adapted to the equipment, Soil samples were taken and parameters such as structure, real density, apparent density, porosity, texture, organic matter, pH, nutrients and cation exchange capacity of the soil were analyzed. For the respective comparison and determination of the percentage of error, a soil sample was sent to the National Institute for Agricultural Research (INIAP). The results obtained from the analysis of the physic-chemical parameters of the soil in the laboratories of the Technical University of Cotopaxi, Campus Salache, show a pH of 8. 34 (moderately basic), structure of 1.13 mm (moderately stable), real density of 2.08 g/cm3 (very low), apparent density of 1.40 g/cm3 (medium), porosity of 31.88 % (low), a sandy loam soil, organic matter of 1. 62% (medium), Na 200 ppm (medium), K 422.5 ppm (high), Ca 2433 ppm (high), NO3 325 ppm (high), electrical conductivity 1363.5 dSm-1 (high) and cation exchange capacity 12.22 meq/100g (medium), it is concluded that through the results of the analysis sent to INIAP and the results obtained in the laboratory analysis practices of the Technical University of Cotopaxi, Campus Salache, very similar results were obtained. Therefore, a proposal for a guide of basic laboratory practices for the analysis of physic-chemical parameters of soil in the laboratory of the Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources is established